Seroprevalence of Severe Acute Respiratory Syndrome Coronavirus 2 Among Skilled Nursing Facility Residents and Staff Members—Los Angeles County, August–September 2020. (24th May 2021) - Malenfant, Jason H; Eslami, Michelle; Dao, Bonnie L; Moore, Leo; Green, Nicole; Silver, David; OYong, Kelsey; Ruparelia, Ashutosh; Fisher, Rebecca; Wood, Julia S; Faisal, Mohammad; Washburn, Faith; et al.
Abstract: Background: The prevalence of current or past coronavirus disease 2019 in skilled nursing facility (SNF) residents is unknown because of asymptomatic infection and constrained testing capacity early in the pandemic. We conducted a seroprevalence survey to determine a more comprehensive prevalence of past coronavirus disease 2019 in Los Angeles County SNF residents and staff members. Methods: We recruited participants from 24 facilities; participants were requested to submit a nasopharyngeal swab sample for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) polymerase chain reaction (PCR) testing and a serum sample for detection of SARS-CoV-2 antibodies. All participants were cross-referenced with our surveillance database to identify persons with prior positive SARS-CoV-2 results. Results: From 18 August to 24 September 2020, we enrolled 3305 participants (1340 residents and 1965 staff members). Among 856 residents providing serum samples, 362 (42%) had current or past SARS-CoV-2 infection. Of the 346 serology-positive residents, 199 (58%) did not have a documented prior positive SARS-CoV-2 PCR result. Among 1806 staff members providing serum, 454 (25%) had current or past SARS-CoV-2 infection. Of the 447 serology-positive staff members, 353 (79%) did not have a documented prior positive SARS-CoV-2 PCR result. Conclusions: Past testing practices and policies missed a substantial number of SARS-CoV-2 infections in SNF residents and staff members. Abstract : Among 24 nursing facilities in Los Angeles County, 42% of residents and 25% of staff had evidence of current/past SARS-CoV-2 infection. Approximately 58% of these residents and 79% of these staff did not have documentation of previously having COVID-19.